Gender Differences in Emotional Intelligence and Social Adjustment among School Students (Journal of Advances and Scholarly Researches in Allied Education, 2025)
The purpose of this study was to investigate the extent to which gender acts as a factor in the relationship between emotional intelligence and social adjustment in children who are of school age. A total of fifty male and fifty female students from a variety of educational institutions comprised the sample. For the purpose of assessing the participants' social adjustment and emotional intelligence, standardized adjustment inventories and an emotional quotient exam were used, respectively. There is a negative link between the two variables, as shown by the fact that students who scored higher on the emotional intelligence exam also scored higher on the social adjustment test. In addition, when it came to the management of typical social and emotional concerns, female students consistently fared better than male students. It was because of their improved capacity to regulate their emotions and adapt to a variety of social situations that they achieved this. Results such as these demonstrate how gender influences emotional intelligence and how essential it is for children of school age to be able to adjust to different social circumstances.